Posterior reversible encephalopathy syndrome in children with malignancies – a single-center retrospective study - Kiermasz, Aleksandra; Zapała, Magdalena; Zwiernik, Bartosz; Stręk-Cholewińska, Angelika; Machnikowska-Sokołowska, Magdalena; Mizia-Malarz, Agnieszka (Frontiers in Neurology, 2023)
Background Posterior reversible encephalopathy syndrome (PRES) diagnosis relies on clinical and radiological characteristics. Clinical manifestations include focal neurologic deficits, hemiparesis, seizures with symptoms of intracranial hypertension, headache, nausea, vomiting, and visual field disturbances. The majority of patients have typical changes in magnetic resonance imaging. The epidemiology and outcomes of PRES in the pediatric cancer population have not been well described. Most of the available data are from retrospective analyses. Objective The aim of our study was to evaluate the clinical and radiological presentation as well as the outcome of PRES in children treated for cancers in a single center. Methods We analyzed data from 1,053 patients diagnosed with malignancies in a single center over 15 years to determine the incidence of PRES. Results 19/1053 (1.8%) patients developed PRES. The diagnosis was accompanied by a range of clinical symptoms including hypertension, seizures, altered mental status, and headaches. Magnetic resonance imaging was performed in all patients, and 14/19 (73.7%) exhibited typical findings consistent with PRES. Four patients (21.0%) required treatment in the Intensive Care Unit. Conclusion Posterior reversible encephalopathy syndrome (PRES) is a rare but significant complication in children with cancer. There is a clear need to establish clinical criteria for PRES to improve the diagnosis and treatment of patients with PRES, particularly in the pediatric oncological population. Further studies are needed to identify the risk factors for recurrent PRES, particularly in pediatric cancer patients undergoing chemotherapy or immunosuppressive treatment.